Secondary battery and electronic device
By adjusting the components of the positive electrode and electrolyte in the secondary battery and combining the titanium element of the titanium dioxide material layer, the shortcomings of the existing secondary batteries in discharge performance and low temperature performance are solved, and higher energy density and longer cycle life are achieved.
Patent Information
- Application Number
- CN202411912642.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-04-01
AI Technical Summary
Existing secondary batteries have shortcomings in discharge performance and low temperature performance, and it is difficult to meet the needs of high energy density and long cycle life.
By adjusting the components of the positive electrode and electrolyte in the secondary battery, lithium iron phosphate and lithium manganate in the positive electrode material layer are used, and ethylene glycol di(propionitrile) ether is added to the electrolyte to combine the titanium element in the titanium dioxide material layer to enhance the crystal structure stability.
It significantly improves the discharge performance and low-temperature performance of the battery, improves the self-discharge rate and capacity retention rate, and extends the cycle life of the battery.
Smart Images

Figure BDA0005207601140000111 
Figure BDA0005207601140000121 
Figure BDA0005207601140000131
Abstract
Description
[0001] This application is a divisional application of a patent application with an application date of September 30, 2024, an application number of 202411379289.2, and an invention name of “Secondary Battery and Electronic Device”. Technical Field
[0002] The present application relates to the field of energy storage, and in particular to a secondary battery and an electronic device. Background Art
[0003] With its core advantages of high energy density and cyclic charge and discharge capabilities, secondary batteries have been widely used in portable electronic devices and electric vehicles. With the advancement of technology and the upgrading of consumer demand, the application boundaries of secondary batteries are also constantly expanding, prompting the industry to continue to focus on the innovative research and development of key battery materials: positive electrodes, negative electrodes, separators and electrolytes. In this process, improving the discharge performance of secondary batteries has become one of the urgent needs in the current application of secondary batteries. Summary of the invention
[0004] The present embodiment further improves the discharge performance by adjusting the composition of the positive electrode and the electrolyte in the secondary battery. The inventor of the present application found that the positive electrode includes a positive electrode current collector and a titanium dioxide material layer and a positive electrode material layer disposed on the positive electrode current collector; the positive electrode material layer includes lithium iron phosphate and lithium manganate, the electrolyte includes ethylene glycol di(propionitrile) ether, the lithium iron phosphate is doped with boron, and the lithium manganate is doped with copper and tin, which can improve the discharge performance of the battery, thereby completing the present application.
[0005] In some embodiments, based on the content of metal elements other than lithium in the positive electrode material layer, the mass content ratio of boron element, copper element and tin element is 130:(1-4):(0.05-0.9).
[0006] In some embodiments, the amount of ethylene glycol di(propionitrile) ether is 0.01 to 1 parts by mass relative to 100 parts by mass of the electrolyte.
[0007] In some embodiments, the amount of ethylene glycol di(propionitrile) ether is 0.05 to 0.9 parts by mass relative to 100 parts by mass of the electrolyte.
[0008] In some embodiments, the amount of ethylene glycol di(propionitrile) ether is 0.09 parts by mass to 0.6 parts by mass relative to 100 parts by mass of the electrolyte.
[0009] In some embodiments, the titanium dioxide material layer is further doped with niobium trioxide.
[0010] In some embodiments, the electrolyte includes 2,4,6-trimethoxyphenyl isocyanate, and the amount of 2,4,6-trimethoxyphenyl isocyanate is 0.01 parts by mass to 2 parts by mass relative to 100 parts by mass of the electrolyte.
[0011] In some embodiments, the electrolyte includes 2,4,6-trifluorophenyl isocyanate, and the amount of 2,4,6-trifluorophenyl isocyanate is 0.1 parts by mass to 4 parts by mass relative to 100 parts by mass of the electrolyte.
[0012] In some embodiments, the electrolyte includes 2,4,6-trimethoxyphenyl isocyanate and 2,4,6-trifluorophenyl isocyanate. Relative to 100 parts by mass of the electrolyte, 2,4,6-trimethoxyphenyl isocyanate is a part by mass, 2,4,6-trifluorophenyl isocyanate is b parts by mass, and 0.1≤a / b≤0.5.
[0013] In another aspect of the present application, the present application provides an electronic device, which includes the secondary battery described in the present application.
[0014] The present application can improve the discharge performance of the battery by using a combination of a specific positive electrode and an electrolyte.
[0015] Additional aspects and advantages of the embodiments of the present application will be described, shown, or explained in part in the subsequent description through implementation of the embodiments of the present application. DETAILED DESCRIPTION
[0016] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the present application.
[0017] Unless expressly stated otherwise, the following terms used in this application have the meanings indicated below.
[0018] The present application can improve the discharge performance of the battery by using a specific combination of a positive electrode and an electrolyte.
[0019] In one embodiment, the present application provides a secondary battery, which includes a positive electrode, a negative electrode, and an electrolyte as described below.
[0020] I. Positive electrode
[0021] The present application relates to a secondary battery and an electronic device. Specifically, the present application provides a secondary battery, which includes: a positive electrode, a negative electrode and an electrolyte, wherein the positive electrode includes a positive electrode current collector and a titanium dioxide material layer and a positive electrode material layer disposed on the positive electrode current collector; the positive electrode material layer includes lithium iron phosphate and lithium manganese oxide, and the electrolyte includes ethylene glycol di(propionitrile) ether. The present application can improve the discharge performance of the battery.
[0022] The positive electrode material layer includes lithium iron phosphate and lithium manganese oxide, and the positive electrode material layer can be one layer or multiple layers.
[0023] The inventor of the present application unexpectedly discovered in the experiment that the positive electrode material layer containing lithium iron phosphate and lithium manganese oxide and the titanium dioxide material layer can cooperate with each other and improve the self-discharge performance and low-temperature discharge performance of the battery in an electrolyte system containing ethylene glycol di(propionitrile) ether. The principle is speculated to be that the titanium element in ethylene glycol di(propionitrile) ether and titanium dioxide can enhance the crystal structure stability of the mixed positive electrode system of lithium iron phosphate and lithium manganese oxide.
[0024] Specifically, from the perspective of improving the discharge performance of the battery, lithium iron phosphate includes boron, and lithium manganese oxide includes copper and tin. From the perspective of improving the self-discharge performance of the battery, the mass content ratio of boron, copper and tin is 130:(1-4):(0.05-0.9), preferably 130:(1-4):(0.1-0.6). When the mass content ratio of boron, copper and tin meets the above range, the discharge performance of the battery can be further improved.
[0025] Specifically, from the perspective of improving the discharge performance of the battery, in some embodiments, based on the content of metal elements other than lithium in the positive electrode material layer, the mass content of the boron element is 1000ppm to 25000ppm, for example, 1000ppm, 2300ppm, 2600ppm, 5300ppm, 6300ppm, 7200ppm, 9500ppm, 10400ppm, 11700ppm, 13600ppm, 15000ppm, 15900ppm, 17900ppm, 19200ppm, 20000ppm, 25000ppm or a value within the range composed of any two of them. In some embodiments, from the perspective of improving battery discharge performance, based on the content of metal elements other than lithium in the positive electrode material layer, the mass content of copper element is 100 ppm to 2000 ppm, for example, 100 ppm, 300 ppm, 500 ppm, 700 ppm, 1000 ppm, 1200 ppm, 1400 ppm, 1500 ppm, 1700 ppm, 1900 ppm, 2000 ppm or a value in the range of any two thereof. In some embodiments, from the perspective of improving battery discharge performance, based on the content of metal elements other than lithium in the positive electrode material layer, the mass content of tin element is 5 ppm to 1000 ppm, for example, 5 ppm, 10 ppm, 50 ppm, 100 ppm, 200 ppm, 300 ppm, 400 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, 900 ppm, 1000 ppm or a value in the range of any two thereof.
[0026] There is no limitation on the type of positive electrode conductive material, and any known conductive material can be used. Examples of positive electrode conductive materials may include, but are not limited to, carbon black such as acetylene black; carbon materials such as amorphous carbon such as needle coke; carbon nanotubes; graphene, etc. The above positive electrode conductive materials may be used alone or in any combination.
[0027] There is no limitation on the type of solvent used to form the positive electrode slurry, as long as it is a solvent that can dissolve or disperse the positive electrode material, the conductive material, and the positive electrode binder. Examples of solvents used to form the positive electrode slurry may include any of aqueous solvents and organic solvents. Examples of aqueous media may include, but are not limited to, water and mixed media consisting of alcohol and water. Examples of organic media may include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, and methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran; amides such as N-methylpyrrolidone, dimethylformamide, and dimethylacetamide; non-protonic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide, etc.
[0028] The density of the active material layer of the positive electrode excluding the current collector is usually 2.5 g / cm 3 In order to further increase the capacity of the battery, it is preferably 2.3 g / cm 3 In addition, as its upper limit, it is preferably 3g / cm 3 the following.
[0029] The type of positive electrode current collector is not particularly limited, and it can be any material known to be suitable for use as a positive electrode current collector. Examples of positive electrode current collectors may include, but are not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and carbon materials such as carbon cloth and carbon paper. In some embodiments, the positive electrode current collector is a metal material. In some embodiments, the positive electrode current collector is aluminum.
[0030] In order to reduce the electronic contact resistance between the positive electrode current collector and the positive electrode material layer, the surface of the positive electrode current collector may include a conductive additive or a conductive coating. Examples of conductive additives may include, but are not limited to, carbon and precious metals such as gold, platinum, and silver. Examples of conductive coatings may include a mixture layer containing an inorganic oxide, a conductive agent, and a binder.
[0031] From the viewpoint of improving the discharge performance of the battery, the titanium dioxide material layer also includes niobium trioxide.
[0032] The positive electrode is made as follows:
[0033] An inorganic additive such as titanium dioxide, a conductive agent such as acetylene black, carbon black, and a binder such as polyvinylidene fluoride or polyacrylonitrile are mixed, and deionized water is added thereto and mixed evenly to prepare a slurry 1.
[0034] The positive electrode material, a conductive agent such as acetylene black or carbon black, and a binder such as polyvinylidene fluoride or polyacrylonitrile are mixed, and a high boiling point solvent such as N-methylpyrrolidone is added thereto and kneaded to prepare a slurry 2 .
[0035] Slurry 1 and slurry 2 are applied onto aluminum foil or the like as a current collector, respectively, dried, and pressed to form a positive electrode.
[0036] II. Electrolyte
[0037] The electrolyte used in the secondary battery of the present application includes an electrolyte and a solvent for dissolving the electrolyte. In some embodiments, the electrolyte of the present application includes ethylene glycol di(propionitrile) ether.
[0038] When ethylene glycol di(propionitrile) ether is used in the battery of the present application, the inventors found that the addition of ethylene glycol di(propionitrile) ether to the positive electrode lithium iron phosphate, lithium manganese oxide and titanium dioxide can improve the discharge performance of the battery.
[0039] Specifically, from the viewpoint of improving the discharge performance of the secondary battery, the electrolyte includes ethylene glycol di (propionitrile) ether, wherein relative to 100 parts by mass of the electrolyte, ethylene glycol di (propionitrile) ether is 0.01 parts by mass or more, preferably 0.05 parts by mass or more, more preferably 0.09 parts by mass or more, and more preferably 0.15 parts by mass or more. In addition, as the upper limit of the content of ethylene glycol di (propionitrile) ether, from the viewpoint of improving the discharge performance of the secondary battery, ethylene glycol di (propionitrile) ether is 1 part by mass or less, preferably 0.9 parts by mass or less, and particularly preferably 0.6 parts by mass or less. When within the above range, it helps to further improve the discharge performance of the secondary battery.
[0040] Specifically, from the viewpoint of improving the discharge performance of the secondary battery, the electrolyte includes 2,4,6-trimethoxyphenyl isocyanate. In some embodiments, relative to 100 parts by mass of the electrolyte, the 2,4,6-trimethoxyphenyl isocyanate is a part by mass, and the value range of a is 0.01 to 2, for example, a is 0.01, 0.03, 0.05, 0.08, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.9, 1, 2 or a value in the range of any two thereof. When the mass fraction of 2,4,6-trimethoxyphenyl isocyanate in the electrolyte is regulated to meet the above range, the discharge performance of the secondary battery can be further improved.
[0041] Specifically, from the viewpoint of improving the discharge performance of the secondary battery, the electrolyte includes 2,4,6-trifluorophenyl isocyanate. In some embodiments, relative to 100 parts by mass of the electrolyte, the 2,4,6-trifluorophenyl isocyanate is b parts by mass, and the value range of b is 0.1 to 4, for example, b is 0.1, 0.2, 0.3, 0.7, 0.8, 1.1, 1.3, 1.6, 1.7, 2.0, 2.1, 2.4, 2.6, 3.0, 4.0 or a value in the range composed of any two of them. When the mass fraction of 2,4,6-trifluorophenyl isocyanate in the electrolyte is regulated to meet the above range, the discharge performance of the secondary battery can be further improved.
[0042] Specifically, from the viewpoint of improving the discharge performance of the secondary battery, the electrolyte includes 2,4,6-trimethoxyphenyl isocyanate and 2,4,6-trifluorophenyl isocyanate. In some embodiments, 0.1≤a / b≤0.5, for example, the value of a / b is 0.1, 0.13, 0.19, 0.27, 0.37, 0.42, 0.46, 0.5 or a value in the range of any two thereof. When the mass fractions of 2,4,6-trimethoxyphenyl isocyanate and 2,4,6-trifluorophenyl isocyanate in the electrolyte are regulated to satisfy the above relationship, the interaction and close cooperation between the two can be promoted, thereby better improving the discharge performance of the secondary battery.
[0043] In some embodiments, the electrolyte additive comprises one or more of the following: ethylene glycol sulfate, 1,2-propylene glycol sulfate, 1,3-propylene glycol sulfate, 1,2-butylene glycol sulfate, 1,3-butylene glycol sulfate, 1,4-butylene glycol sulfate, 1,2-pentanediol sulfate, 1,3-pentanediol sulfate, 1,4-pentanediol sulfate, 1,5-pentanediol sulfate, dimethyl sulfate, ethyl methyl sulfate, diethyl sulfate, methyl fluorosulfonate, ethyl trifluoromethanesulfonate, methyl methanesulfonate, ethyl methanesulfonate, dibutylenesulfonate. Esters, methyl 2-(methylsulfonyloxy)propionate, ethyl 2-(methylsulfonyloxy)propionate, 1-fluoro-1,3-propane sultone, 2-fluoro-1,3-propane sultone, 3-fluoro-1,3-propane sultone, 1-methyl-1,3-propane sultone, 2-methyl-1,3-propane sultone, 3-methyl-1,3-propane sultone, 1-propylene-1,3-sultone, 2-propylene-1,3-sultone, 1-fluoro-1-propylene-1,3-sultone, 2-fluoro-1-propylene-1,3-sultone, 3 -1-fluoro-1-propylene-1,3-sultone, 1-fluoro-2-propylene-1,3-sultone, 2-fluoro-2-propylene-1,3-sultone, 3-fluoro-2-propylene-1,3-sultone, 1-methyl-1-propylene-1,3-sultone, 2-methyl-1-propylene-1,3-sultone, 3-methyl-1-propylene-1,3-sultone, 1-methyl-2-propylene-1,3-sultone, 2-methyl-2-propylene-1,3-sultone, 3-methyl-2-propylene-1,3-sultone Lactone, 1,4-butane sultone, 1,5-pentane sultone, methylene methane disulfonate, ethylene methane disulfonate, dimethyl sulfite, ethyl methyl sulfite, diethyl sulfite, 1,2-ethylene glycol sulfite, 1,2-propylene glycol sulfite, 1,3-propylene glycol sulfite, 1,2-butylene glycol sulfite, 1,3-butylene glycol sulfite, 1,4-butylene glycol sulfite, 1,2-pentanediol sulfite, 1,3-pentanediol sulfite, 1,4-pentanediol sulfite, 1,5-pentanediol sulfite, etc. In some embodiments, the electrolyte further includes an ionizable lithium salt, and the ionizable lithium salt includes at least one of LiPF6, LiSbF6, LiAsF6, LiClO4, LiN(C2F5SO2)2, CF3SO3Li, LiC(CF3SO2)3 or LiC4BO8. For example, the lithium salt used in the electrolyte of the present application includes LiPF6, and the content of LiPF6 is 9 to 15% by mass, preferably 9 to 13% by mass, and more preferably 9 to 12% by mass based on the mass of the electrolyte. By setting the content range as above, the effect of improving the discharge performance of the battery can be more balanced.
[0044] In some embodiments, the electrolyte also includes at least one of ethylene glycol di(propionitrile) ether (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium bis(oxalatoborate) (LiBOB), lithium tetrafluoroborate (LiBF4), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), and lithium bis(fluorosulfonyl)imide (LiFSI).
[0045] In some embodiments, the additive in the electrolyte further includes at least one of a fluoroether compound, a fluorocarbonate compound, and an ether nitrile compound, such as hydrofluoroether (HFE-458), fluoroethylene carbonate (FEC), and the like.
[0046] In some embodiments, the electrolyte may further include a non-aqueous solvent. The non-aqueous solvent may be selected from carbonate compounds, carboxylate compounds, ether compounds, phosphate compounds, other organic solvents, or combinations thereof.
[0047] Optionally, the carbonate compound may be a linear carbonate compound, a cyclic carbonate compound or a combination thereof. On the other hand, the carbonate compound may also be a fluorinated carbonate compound, a non-fluorinated carbonate compound or a combination thereof.
[0048] Specifically, examples of chain carbonate compounds are diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) or combinations thereof. Examples of fluorocarbonate compounds are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate or combinations thereof.
[0049] Specifically, examples of the carboxylate compound are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, methyl formate, or a combination thereof.
[0050] Specifically, examples of the ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or a combination thereof.
[0051] Specifically, examples of the phosphate compound are trimethyl phosphate, triethyl phosphate, trioctyl phosphate, or a combination thereof.
[0052] Specifically, examples of other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methylpyrrolidone, formamide, dimethylformamide, acetonitrile, or a combination thereof.
[0053] III. Negative electrode
[0054] The negative electrode includes a negative electrode current collector and a negative electrode material layer disposed on the surface of the negative electrode current collector, wherein the negative electrode material layer contains a negative electrode material. In some embodiments, the chargeable capacity of the negative electrode material is greater than the discharge capacity of the positive electrode material to prevent lithium metal from being accidentally precipitated on the negative electrode during charging.
[0055] The negative electrode material is not particularly limited, and examples thereof include carbon-based negative electrode materials, metal-based negative electrode materials, silicon-based negative electrode materials, and negative electrode materials in combination thereof.
[0056] Carbon-based negative electrode materials
[0057] Here, the carbon-based negative electrode material refers to an active material having a carbon-based skeleton into which lithium can be inserted, and examples of the carbon-based negative electrode material include carbonaceous materials and graphite materials.
[0058] As carbonaceous materials, for example, graphitizable carbon, non-graphitizable carbon having a structure similar to an amorphous structure represented by glassy carbon, etc. can be cited. Here, as graphitizable carbon, for example, carbon materials obtained from petroleum or coal using tar pitch as a raw material can be cited. When giving specific examples, coke, mesocarbon microbeads (MCMB), mesophase pitch-based carbon fibers, and pyrolysis vapor-grown carbon fibers can be cited. In addition, as non-graphitizable carbon, for example, phenolic resin sintered bodies, polyacrylonitrile-based carbon fibers, quasi-isotropic carbon, furfuryl alcohol resin sintered bodies (PFA), hard carbon, etc. can be cited.
[0059] Furthermore, as graphite materials, for example, natural graphite, artificial graphite, etc. can be cited. Among them, as artificial graphite, for example: artificial graphite obtained by heat-treating carbon containing graphitized carbon mainly at 2800°C or above, graphite MCMB obtained by heat-treating MCMB at 2000°C or above, graphite mesophase pitch-based carbon fiber obtained by heat-treating mesophase pitch-based carbon fiber at 2000°C or above, etc. can be cited. In addition, in the present application, as a carbon-based negative electrode material, natural graphite (amorphous coated natural graphite) in which at least a portion of its surface is coated with amorphous carbon can be used.
[0060] In addition, the metal-based negative electrode material is an active material containing a metal, generally referring to an active material having an element capable of inserting lithium or alloying with lithium in the structure, an element capable of inserting lithium or alloying with lithium, and a theoretical current capacity of 500 mAh / g or more per unit mass. As a metal-based negative electrode material, for example, lithium metal, a single metal capable of forming a lithium alloy (such as Ag, Al, Ba, Bi, Cu, Ga, Ge, In, Ni, P, Pb, Sb, Si, Sn, Sr, Zn, Ti, etc.) and its alloy, and their oxides, sulfides, nitrides, silicides, carbides, phosphides, etc. can be used. Among them, as a metal-based negative electrode material, an active material (silicon-based negative electrode material) containing silicon is preferably used. This is because the use of a silicon-based negative electrode material can increase the capacity of a secondary battery.
[0061] Examples of silicon-based negative electrode materials include silicon (Si), alloys containing silicon, SiO, SiO 2 , and composites of silicon-containing materials and conductive carbon (silicon-carbon materials) in which a silicon-containing material is coated with conductive carbon or composited with conductive carbon.
[0062] From the viewpoint of improving battery capacity, a silicon-carbon material, for example, a porous carbon-supported silicon composite material is preferred.
[0063] The negative electrode material may be used alone or in combination of two or more at any ratio.
[0064] Here, the volume average particle size of the negative electrode material is preferably 1 μm or more, more preferably 5 μm or more, and is preferably 30 μm or less, more preferably 20 μm or less.
[0065] The negative electrode material layer may further include a negative electrode binder. The negative electrode binder can improve the bonding between the negative electrode material particles and the bonding between the negative electrode material and the current collector. The type of negative electrode binder is not particularly limited, as long as it is a material that is stable to the solvent used in the electrolyte or electrode manufacturing. In some embodiments, the negative electrode binder includes a resin binder. Examples of resin binders include, but are not limited to, fluororesins, polyacrylonitrile (PAN), polyimide resins, acrylic resins, polyolefin resins, and the like. When an aqueous solvent is used to prepare the negative electrode mixture slurry, the negative electrode binder includes, but is not limited to, carboxymethyl cellulose (CMC) or its salt, styrene-butadiene rubber (SBR), polyacrylic acid (PAA) or its salt, polyvinyl alcohol, and the like.
[0066] As a current collector for holding the negative electrode material, any known current collector can be used. Examples of negative electrode current collectors include, but are not limited to, metal materials such as copper, nickel, stainless steel, and nickel-plated steel. In some embodiments, the negative electrode current collector is copper.
[0067] The negative electrode can be prepared by applying a negative electrode mixture slurry containing a negative electrode material, a resin binder, etc. on a negative electrode current collector, drying it, and then rolling it to form a negative electrode material layer on both sides of the negative electrode current collector, thereby obtaining a negative electrode.
[0068] IV. Isolation membrane
[0069] In order to prevent short circuit, a separator is usually provided between the positive electrode and the negative electrode. In this case, the electrolyte of the present application is usually used by infiltrating the separator.
[0070] There is no particular restriction on the material and shape of the isolation membrane, as long as the effect of the present application is not significantly impaired. The isolation membrane may be a resin, glass fiber, inorganic substance, etc. formed of a material that is stable to the electrolyte of the present application. In some embodiments, the isolation membrane includes a porous sheet or a non-woven fabric-like material with excellent liquid retention. Examples of materials for resin or glass fiber isolation membranes may include, but are not limited to, polyolefins, aromatic polyamides, polytetrafluoroethylene, polyether sulfone, etc. In some embodiments, the polyolefin is polyethylene or polypropylene. In some embodiments, the polyolefin is polypropylene. The materials of the above isolation membranes may be used alone or in any combination.
[0071] The isolation film may also be a material formed by laminating the above materials, and examples thereof include, but are not limited to, a three-layer isolation film formed by laminating polypropylene, polyethylene, and polypropylene in this order.
[0072] Examples of inorganic materials may include, but are not limited to, oxides such as aluminum oxide and silicon dioxide, nitrides such as aluminum nitride and silicon nitride, and sulfates (e.g., barium sulfate, calcium sulfate, etc.) The form of the inorganic material may include, but is not limited to, granular or fibrous.
[0073] The separator may be in the form of a thin film, examples of which include, but are not limited to, nonwoven fabrics, woven fabrics, microporous films, etc. In the thin film form, the separator has a pore size of 0.01 μm to 1 μm and a thickness of 5 μm to 50 μm. In addition to the above-mentioned independent thin film separators, the following separators may also be used: a separator formed by forming a composite porous layer containing the above-mentioned inorganic particles on the surface of the positive electrode and / or the negative electrode using a resin-based adhesive, for example, a separator formed by using a fluororesin as an adhesive to form a porous layer on both sides of the positive electrode with aluminum oxide particles having a particle size of 90% less than 1 μm.
[0074] The thickness of the isolation film is arbitrary. In some embodiments, the thickness of the isolation film is greater than 1 μm, greater than 5 μm, or greater than 8 μm. In some embodiments, the thickness of the isolation film is less than 50 μm, less than 40 μm, or less than 30 μm. When the thickness of the isolation film is within the above range, the insulation and mechanical strength can be ensured, and the DC resistance characteristics and energy density of the secondary battery can be ensured.
[0075] The present application further provides an electronic device, which includes the secondary battery described in the present application.
[0076] The use of the secondary battery of the present application is not particularly limited, and it can be used for any electronic device known in the prior art. In some embodiments, the secondary battery of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.
[0077] Example
[0078] Examples of the secondary battery of the present application are shown below, but the present application is not limited to these examples.
[0079] Preparation of secondary batteries
[0080] Production of positive electrode:
[0081] 70% by mass of titanium dioxide, 10% by weight of acetylene black, and 20% by weight of polyvinylidene fluoride were mixed, and deionized water was added thereto and mixed evenly to prepare positive electrode slurry 1. The slurry was applied on both sides of a positive electrode current collector aluminum foil with a thickness of 10 μm and dried to form a titanium dioxide material layer.
[0082] The positive electrode materials lithium iron phosphate (46wt%), LiMn2O4 (51wt%), and conductive carbon black (1wt%) in Table 1 were mixed, and polyvinylidene fluoride (2wt%) was dissolved in N-methylpyrrolidone to obtain a solution and mixed to prepare positive electrode slurry 2. The positive electrode slurry 2 was evenly coated on the surface of the titanium dioxide material layer on both sides of the positive electrode current collector aluminum foil, and then cold pressed, cut and slit to obtain a positive electrode.
[0083] Preparation of isolation membrane: A 12 μm thick polyethylene (PE) microporous membrane was selected as the isolation membrane.
[0084] Negative electrode production:
[0085] The negative electrode material artificial graphite and SiO2 (mass ratio 90:10): 96wt%, styrene-butadiene rubber: 2wt% are mixed, added to a solution obtained by dissolving 2wt% of lithium carboxymethyl cellulose in deionized water in advance and mixed to prepare a negative electrode slurry. The negative electrode slurry is coated on one side of a copper foil, dried, pressurized, and then cut into a specified size to make a negative electrode.
[0086] Preparation of electrolyte: In an argon atmosphere glove box with a water content of less than 10 ppm, ethyl methyl carbonate, ethyl acetate, and ethylene carbonate are mixed in a mass ratio of 1:1:1 to obtain a basic solvent, and then lithium salt LiPF6 and the additives shown in Table 1 are added to the above-mentioned base solvent, and the electrolyte is obtained after mixing evenly, wherein the mass content of LiPF6 is 12% based on the mass of the electrolyte.
[0087] Battery production:
[0088] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the electrode assembly is wound, and the electrode assembly is placed in the outer packaging aluminum plastic film after welding the pole ear, and the water is removed at 80°C, and the above electrolyte is injected, and the lithium ion battery is obtained after vacuum packaging, standing, formation, shaping, capacity testing and other processes. The secondary battery is a bag-shaped battery with a width of 30mm, a height of 45mm, and a thickness of 5mm.
[0089] Table 1
[0090]
[0091]
[0092]
[0093] Test Method
[0094] Normal temperature discharge performance
[0095] A reference battery is prepared for reference. The reference battery is the same as the battery of Example 1 except that it does not contain a titanium dioxide material layer, does not contain ethylene glycol di(propionitrile) ether, and the positive electrode material does not contain lithium iron phosphate (only contains lithium manganate). The obtained reference battery is charged at a constant current of 0.05C at a temperature environment of 25°C until the battery voltage reaches 3.6V. Then, it is discharged at a constant current of 0.05C until the battery voltage reaches 2.5V, and the charge and discharge curve is obtained. It is left to stand in an open circuit state for 20 minutes between charging and discharging.
[0096] The prepared batteries of each embodiment and comparative example were clamped by a pair of stainless steel (thickness 2mm) clamps and fixed with a pressure of 0.2MPa. First, the battery was charged at a constant current of 0.3C until the voltage reached 3.6V in a temperature environment of 25°C, and then charged at a constant voltage of 3.6V until the current reached 0.02C. Next, the battery was stored in a temperature environment of 25°C, and the battery voltage V1 after 48 hours and the battery voltage V2 after 72 hours were measured.
[0097] Based on the charge / discharge curve of the reference battery, the charge state SOC1 after 48 hours and the charge state SOC2 after 72 hours were obtained from the battery voltages V1 and V2. Next, the self-discharge rate sd per day was derived and evaluated based on the following formula.
[0098] Self-discharge rate sd (% / day) = SOC1 (%) - SOC2 (%).
[0099] The smaller the self-discharge rate is, the better the discharge performance of the secondary battery in the present application is.
[0100] A: The self-discharge rate sd (% / day) is less than 2.
[0101] B: The self-discharge rate sd (% / day) is 2 or more and less than 4.
[0102] C: The self-discharge rate sd (% / day) is 4 or more and less than 7.
[0103] D: The self-discharge rate sd (% / day) is 7 or more.
[0104] Low temperature discharge performance
[0105] After the lithium-ion battery is charged to 3.6V at a constant current of 990mA (0.3 hour rate) at an ambient temperature of 25°C, it is charged at a constant voltage of 3.6V with a termination current of 66mA. Then, it is discharged to 2.5V at a constant current of 3300mA (1.0 hour rate), and the discharge capacity at this time is measured as the battery capacity at 25°C. Then, it is charged to 3.6V at a constant current of 990mA (0.3 hour rate) at an ambient temperature of 25°C, and charged to 3.6V at a constant voltage of 3.6V with a termination current of 66mA, and then placed in an environment of -10°C for 2 hours. Then, it is discharged to 2.5V at a constant current of 3300mA (1.0 hour rate) at an ambient temperature of -10°C, and the discharge capacity at this time is measured as the battery capacity at -10°C. The -10°C temperature discharge capacity retention rate was calculated by the following formula: -10°C discharge capacity retention rate (%) = (-10°C battery capacity / 25°C battery capacity) x 100%.
[0106] The calculated -10°C discharge capacity retention rate is used to evaluate the low-temperature discharge performance of the lithium-ion battery. The higher the low-temperature discharge capacity retention rate, the better the low-temperature discharge performance of the lithium-ion battery.
[0107] A: -10°C discharge capacity retention rate (%) is 85 or more.
[0108] B: -10°C discharge capacity retention rate (%) is 80 or more and less than 85.
[0109] C: -10°C discharge capacity retention rate (%) is 72 or more and less than 80.
[0110] D: -10℃ discharge capacity retention rate (%) is less than 72.
[0111] Test Results
[0112] In Table 1, “ / ” indicates that the substance was not added;
[0113] It can be seen from Table 1 that the positive electrode of the present application includes a positive electrode collector and a titanium dioxide material layer and a positive electrode material layer arranged on the positive electrode collector; the positive electrode material layer includes lithium iron phosphate and lithium manganese oxide, and the electrolyte includes ethylene glycol di(propionitrile) ether, which can improve the discharge performance of the battery.
[0114] In particular, the present application dopes boron into lithium iron phosphate and copper and tin into lithium manganese oxide, which can further improve the battery discharge performance.
[0115] In particular, based on the content of metal elements other than lithium in the positive electrode material layer, the mass content ratio of boron, copper and tin is 130:(1-4):(0.05-0.9), which can further improve the battery discharge performance.
[0116] In particular, the amount of ethylene glycol di(propionitrile) ether is 0.01 to 1 parts by mass relative to 100 parts by mass of the electrolyte, which can further improve the discharge performance of the battery.
[0117] In particular, the amount of ethylene glycol di(propionitrile) ether is more preferably 0.09 to 0.6 parts by mass relative to 100 parts by mass of the electrolyte, which can further improve the discharge performance of the battery.
[0118] In particular, the electrolyte includes other additives, which can further improve the battery discharge performance.
[0119] In particular, the titanium dioxide material layer also includes niobium trioxide, which can further improve the discharge performance of the battery.
[0120] In particular, the electrolyte includes 2,4,6-trimethoxyphenyl isocyanate, and the amount of 2,4,6-trimethoxyphenyl isocyanate is 0.01 parts by mass to 2 parts by mass relative to 100 parts by mass of the electrolyte, which can further improve the battery discharge performance.
[0121] In particular, the electrolyte includes 2,4,6-trifluorophenyl isocyanate, and the amount of 2,4,6-trifluorophenyl isocyanate is 0.1 parts by mass to 4 parts by mass relative to 100 parts by mass of the electrolyte, which can further improve the battery discharge performance.
[0122] In particular, the electrolyte includes 2,4,6-trimethoxyphenyl isocyanate and 2,4,6-trifluorophenyl isocyanate. Relative to 100 parts by mass of the electrolyte, 2,4,6-trimethoxyphenyl isocyanate is a part by mass, 2,4,6-trifluorophenyl isocyanate is b parts by mass, and 0.01≤a / b≤0.5 can further improve the battery discharge performance.
[0123] References to "embodiments", "partial embodiments", "one embodiment", "another example", "example", "specific example" or "partial example" throughout the specification mean that at least one embodiment or example in the present application includes the specific features, structures, materials or characteristics described in the embodiment or example. Therefore, descriptions appearing in various places throughout the specification, such as: "in some embodiments", "in an embodiment", "in one embodiment", "in another example", "in an example", "in a specific example" or "example", do not necessarily refer to the same embodiment or example in the present application. In addition, the specific features, structures, materials or characteristics in the present application may be combined in one or more embodiments or examples in any suitable manner.
[0124] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.
Claims
1. A secondary battery comprising: A positive electrode, a negative electrode and an electrolyte, characterized in that The positive electrode includes a positive electrode collector and a titanium dioxide material layer and a positive electrode material layer arranged on the positive electrode collector; the titanium dioxide material layer is located between the positive electrode collector and the positive electrode material layer, the positive electrode material layer includes lithium iron phosphate and lithium manganese oxide, and the electrolyte includes ethylene glycol di(propionitrile) ether; wherein relative to 100 parts by mass of the electrolyte, the ethylene glycol di(propionitrile) ether is 0.05 parts by mass to 0.9 parts by mass.
2. The secondary battery according to claim 1, characterized in that: The lithium iron phosphate is doped with boron, and the lithium manganese oxide is doped with copper and tin.
3. The secondary battery according to claim 2, characterized in that: Wherein, based on the content of metal elements other than lithium in the positive electrode material layer, the mass content ratio of the boron element, the copper element and the tin element is 130:(1-4):(0.05-0.9).
4. The secondary battery according to any one of claims 1 to 3, characterized in that: The amount of ethylene glycol di(propionitrile) ether is 0.09 to 0.6 parts by mass relative to 100 parts by mass of the electrolyte.
5. The secondary battery according to any one of claims 1 to 3, characterized in that: The titanium dioxide material layer is further doped with niobium trioxide.
6. The secondary battery according to any one of claims 1 to 3, characterized in that: wherein the electrolyte comprises 2,4,6-trimethoxyphenyl isocyanate, and the amount of the 2,4,6-trimethoxyphenyl isocyanate is 0.01 parts by mass to 2 parts by mass relative to 100 parts by mass of the electrolyte; or The electrolyte solution includes 2,4,6-trifluorophenyl isocyanate, and the amount of the 2,4,6-trifluorophenyl isocyanate is 0.1 parts by mass to 4 parts by mass relative to 100 parts by mass of the electrolyte solution.
7. The secondary battery according to any one of claims 1 to 3, characterized in that: The electrolyte comprises 2,4,6-trimethoxyphenyl isocyanate and 2,4,6-trifluorophenyl isocyanate. Relative to 100 parts by mass of the electrolyte, the 2,4,6-trimethoxyphenyl isocyanate is a part by mass, the 2,4,6-trifluorophenyl isocyanate is b parts by mass, and 0.1≤a / b≤0.
5.
8. An electronic device, characterized in that: It includes the secondary battery according to any one of claims 1 to 7.